2023
DOI: 10.37034/infeb.v5i1.193
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Rebranding Produk Property Pada Perumahan dalam Meningkatkan Kredibilitas Pembeli Pada PT. Cendana Indo Pratama

Abstract: Cendana Indo Pratama is a company engaged in the General Contractor field, among the business units developed by PT. Cendana Indo Pratama, one of which is in the property sector which is currently being built, namely the Bimura Residence housing in the Paiton area, as we know many residential businesses have been built, especially in the Paiton area, East Java. In early 2022 PT. Cendana Indo Pratama is rebranding the Bimura Residence housing. The purpose of this research is to describe the basic subsidy rebran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…The results of the study also state that customers remain loyal to brands that have experienced rebranding so it can be concluded that rebranding has positive impact on customer loyalty. In research conducted by Cahyaningtiyas et al (2023), conducted research on rebranding efforts and factors in increasing buyer credibility at Bimura Residence. This research utilizes qualitative approach, involves interviews as the chosen data collection technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study also state that customers remain loyal to brands that have experienced rebranding so it can be concluded that rebranding has positive impact on customer loyalty. In research conducted by Cahyaningtiyas et al (2023), conducted research on rebranding efforts and factors in increasing buyer credibility at Bimura Residence. This research utilizes qualitative approach, involves interviews as the chosen data collection technique.…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaire from Google Forms will be used as an instrument for the data collection, also similar to the method used by (Prayoga & Suseno, 2020). The qualitative approach will also be used in this study by using data collection techniques through interviews similar to research conducted by (Cahyaningtiyas et al, 2023). The data analysis technique used for this study is linear regression analysis, similar to research by (Ardiansyah & Chanrico, 2023).…”
Section: Introductionmentioning
confidence: 99%